Assess the Barrier of Small and Medium-Sized Hotel Digitalization: A Combination of AHP and DEMATEL Analysis - TUNG, Pham Thanh (Journal of Environmental Management and Tourism, 2024)
This study investigates the barriers to digitalization in small and medium-sized hotels through a combined Analytic Hierarchy Process (AHP) and Decision-Making Trial and Evaluation Laboratory (DEMATEL) analysis. It aims to identify and rank the barriers to technology adoption and understand their interrelationships. The findings emphasize that the most significant barriers are technological context and organizational context, precisely data security, IT infrastructure, competition, skilled digital workforce, and financial resources are challenges for this process. Besides, the technological context and organizational context belong to the cause group, which directly and indirectly influences the environmental context. The study provides a comprehensive framework for understanding the multifaceted barriers to digitalization in the hotel industry, suggesting that managers focus on overcoming these critical barriers to improve performance through digital adoption. This research solves a gap in the literature by focusing on independent hotels' challenges in technology adoption. It offers practical insights for hotel managers and technology developers aiming to support digitalization in this industry.